Modelling and Characterization of Laterally-Coupled Distributed Feedback Laser and Semiconductor Optical Amplifier - Nkanta, Julie Efiok (Université d'Ottawa / University of Ottawa, 2016)
There is an increasing need for tuneable spectrally pure semiconductor laser sources as well as broadband and polarization insensitive semiconductor optical amplifiers based on the InGaASP/InP material system, to be monolithically integrated with other active and passive components in a photonic integrated circuit. This thesis aims to contribute to finding a solution through modelling, experimental characterization and design improvements. In this thesis we have analyzed laterally-coupled distributed feedback (LC-DFB) lasers. These lasers have the gratings etched directly out of the ridge sidewalls thus lowering the cost associated with the re-growth process required if the gratings were otherwise embedded above the active region. The performance characteristics are analyzed for the LC-DFB lasers partitioned into 1-, 2-, and 3-, electrodes with individual bias control at various operating temperatures. The laser exhibits a stable single mode emission at 1560 nm with a current tuning rate of ~14 pm/mA for a tuning of 2.25 nm. The side modes are highly suppressed with a maximum side-mode suppression ratio of 58 dB. The light-current characteristics show a minimum 40 mA threshold current, and power saturation occurring at higher injection currents. The linewidth characteristics show a minimum Lorentzian linewidth of 210 kHz under free-running and further linewidth reduction under feedback operation. The multi-electrode LC-DFB laser devices under appropriate and selective driving conditions exhibit a flat frequency modulation response from 0 to above 300 MHz. The multi-electrode configuration can thus be further exploited for certain requirements. Simulation results and design improvements are also presented. The experimental characterization of semiconductor optical amplifier (SOA) and Fabry-Perot (FP) laser operating in the E-band are also presented. For the SOA, the linear vertical and horizontal states of polarization corresponding to the transverse electric (TE) and transverse magnetic (TM) modes were considered. For various input power and bias, performance characteristics shows a peak gain of 21 dBm at 1360 nm, gain bandwidth of 60 nm and polarization sensitivity of under 3 dB obtained for the entire wavelength range analyzed from 1340 to 1440 nm. The analysis presented in this thesis show good results with room for improvement in future designs.
Keywords: Semiconductors; Distributed feedback laser; Semiconductor optical amplifier; Fabry-Perot laser; Photonics; Polarization independence; multi-electrode; laterally_coupled